Parental Divorce, Family Conflict and Adolescent Depression and Anxiety - Hildur Pálmarsdóttir 1992- (2015)
Both parental divorce and family conflict can be stressful life events in adolescents‘ lives. Today, parental divorce is more common than in the past and more than one million children experience parental divorce every year. Researches have shown that adolescents’ of divorced parents and those who experience family conflict have more psychological problems than other adoloscents. In this research we look at how parental divorce and family conflict can affect children‘s depression and anxiety and how effects of parental divorce on adolescent depression and anxiety are mediated through family conflict. This study was a population-based, cross-sectional survey entitled Youth in Iceland and was conducted by the Icelandic Centre for Social Research and Analysis at Reykjavik University in February, 2012. The sample was based on 2215 8th to 10th grade students. Using multiple regression models, findings show that family conflict and parental divorce affect adolescents‘ depression and anxiety. Key words: parental divorce, family conflict, depression, anxiety Bæði skilnaður foreldra og fjölskylduágreiningur geta haft mikil áhrif á líf unglinga. Skilnaður er algengari nú til dags heldur en áður fyrr og ástæðan fyrir því gæti verið sú að viðhorf til skilnaða hefur breyst. Rannsóknir hafa sýnt að þeir unglingar sem eiga foreldra sem hafa skilið og þeir sem upplifa fjölskylduágreining glíma við fleiri sálfræðileg vandamál en aðrir unglingar. Í þessari rannsókn verður skoðað hvernig skilnaður foreldra og fjölskylduágreiningur getur haft áhrif á þunglyndi og kvíða unglinga. Einnig hvernig áhrifin af skilnaði á kvíða og þunglyndi unglinga sé miðlað í gegnum fjölskyldu ágreining. Þetta er þversniðsrannsókn sem ber titilinn Ungt fólk og var hún framkvæmd af Rannsóknum og greiningu í febrúarmánuði árið 2012. Úrtak rannsóknarinnar er byggt á 2215 8. til 10. bekkjar nemendum í grunnskólum landsins. Línuleg aðhvarfsgreining var notuð í úrvinnslu á niðustöðum rannsóknarinnar og sýna þær niðurstöður að fjölskylduágreiningu og ...